2014
DOI: 10.1021/pr500847p
|View full text |Cite
|
Sign up to set email alerts
|

C1QBP Negatively Regulates the Activation of Oncoprotein YBX1 in the Renal Cell Carcinoma As Revealed by Interactomics Analysis

Abstract: The Y-box-binding protein 1 (YBX1) plays a critical role in tumorigenesis by promoting cell proliferation, overriding cell-cycle check points, and enhancing genomic instability. In this study, the interactome of YBX1 in renal cell carcinoma (RCC) was analyzed by coimmunoprecipitation and mass spectrometry to better understand its function and regulatory mechanism. A total of 129 proteins were identified as potential YBX1 binding partners. The interaction between the complement component 1, q subcomponent bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
9
19
0
1
Order By: Relevance
“…Our results revealed C1QBP as another factor that could interact with and influence the nuclear translocation of YBX1. This is consistent with their expression pattern showing the expression of C1QBP is negatively correlated with YBX1 nuclear localization in RCC samples [33]. Importantly, our finding that C1QBP might function through YBX1 to modulate AR expression provides a good model of how C1QBP/YBX1 might influence the RCC cell invasion.…”
Section: Discussionsupporting
confidence: 89%
“…Our results revealed C1QBP as another factor that could interact with and influence the nuclear translocation of YBX1. This is consistent with their expression pattern showing the expression of C1QBP is negatively correlated with YBX1 nuclear localization in RCC samples [33]. Importantly, our finding that C1QBP might function through YBX1 to modulate AR expression provides a good model of how C1QBP/YBX1 might influence the RCC cell invasion.…”
Section: Discussionsupporting
confidence: 89%
“…Among the 13 identified survival-associated SFs, HNRNPU, PTBP1, and YBX1 have already been revealed in several RCC-related pathways based on previous studies. [55][56][57] These results suggested that our analyses were partly in accordance with previous research. 53 Besides, in vitro and in vivo studies have revealed that PTBP1 could promote tumor angiogenesis and distal metastasis via activating the hypoxia-inducible factor-1α pathway, indicating its important prognostic role in RCC.…”
Section: Discussionsupporting
confidence: 92%
“…But it has also been documented that C1QBP is significantly decreased in human cervical squamous cell carcinoma tissues relative to normal cervix tissues and inhibits viability, migration and proliferation of cervical squamous cells carcinoma via the p38 MAPK signaling pathway 9 . Consistent with the finding in cervical squamous cell carcinoma, our study 10 shows that the level of C1QBP in the renal carcinoma tissues is significantly lower than that in the adjacent normal tissues, and the expression of C1QBP could be used as an independent prognostic maker for cancer progression in the renal cell carcinoma (RCC) patients. In a word, it is tissue specificity of C1QBP expression and C1QBP appears to be tumor suppresser in RCC.…”
Section: Introductionsupporting
confidence: 89%
“…Because of the complicated mechanisms of tumor development, there’s much to explore for development of potential targeted therapies for RCC as well as discovery of new biomarkers for RCC staging and prognosis. In the previous study 10 , immunohistochemistry and western blotting are used to study the expression of C1QBP in renal carcinoma tissue and cells, the expression of C1QBP in renal carcinoma tissue is lower compared with para-carcinoma tissue. We further examined the potential biological consequence of a lowered expression of C1QBP in this study.…”
Section: Discussionmentioning
confidence: 99%